PENGAWASAN TERHADAP PENYELENGGARAAN PERJALANAN IBADAH UMRAH (Studi Terhadap Kasus PT. Firs Anugrah Karya Wisata) - ADHI PRADANA PUTRA, S.H. A.2021151036, JURNAL MAHASISWA S2 HUKUM UNTAN (Jurnal NESTOR Magister Hukum, 2018)
ABSTRACTThis thesis discusses the Supervision Against the Implementation of Umrah Worship Trip (Study Against The Case of PT Firs Anugrah Karya Wisata). The approach method used in this research is the normative juridical approach. From the result of this thesis research, it can be concluded that the form of supervision conducted by the government towards the implementation of umrah based on the prevailing laws and regulations in Indonesia in the supervision and control of the implementation of umrah is one of the duties of the Ministry of Religious Affairs in accordance with Regulation of the Minister of Religious Affairs Number 18 of 2015 Article 20 Paragraph (1) and Paragraph (2) stated that the supervision shall be conducted by the Director General on behalf of the Minister. Supervision includes oversight of travel plans, Jemaah service operational activities, compliance and / or control over the provisions of legislation and regulations. In order to improve the supervision function of the service to Jemaah Umrah, the Ministry of Religious Affairs through the Directorate General of Hajj and Umrah Implementation regularly conduct monitoring at Soekarno Hatta airport. Every day assigned personnel from the Ministry of Religious Affairs with Airport Police to directly supervise Jemaah service activities at the airport. MoU Kemenag with Polri has been running since 2013 and always give full support. Improving the supervision of umrah. Supervision is done because of the many travel agencies that provide services Umrah in Indonesia, currently the government is more focused on the implementation of the pilgrimage so hand over Umrah through travel agencies. Meanwhile, the ministry of religion is only authorized to grant business licenses. As for the factors that led to weak supervision by the ministry of religion against the implementation of umroh worship in relation to the case of PT. Firs the blessings of the tour are Travel Permit Umroh, and the rules that have not been able to meet consumer protection.Adapun the efforts made by the ministry of religion to increase supervision over the business travel agency umroh in order to protect the congregation With its form as a limited liability company, First Travel is a legal entity, therefore a legal subject having rights and obligations. As a legal subject, First Travel has a legal liability for alleged criminal acts committed against prospective pilgrims and Umrah, responsibilities relating to the concept of legal obligations. A person is legally responsible for a particular act or that he or she assumes legal liability means that he or she is responsible for a sanction in the event of a conflicting action. From legal aspect, First Travel's legal responsibility can be seen from civil, criminal, and administrative aspects. Keywords: Supervision, Implementation of Travel, Umrah Worship.    ABSTRAKTesis ini membahas tentang Pengawasan Terhadap Penyelenggaraan Perjalanan Ibadah Umrah (Studi Terhadap Kasus PT.  Firs Anugrah Karya Wisata). Metode pendekatan yang digunakan dalam penelitian ini adalah pendekatan yuridis normatif. Dari hasil penelitian tesis ini diperoleh kesimpulan bahwa Bentuk pengawasan yang dilakukan oleh pemerintah terhadap penyelenggaraan umrah berdasarkan peraturan perundang-undangan yang berlaku di Indonesia dalam Pengawasan dan pengendalian penyelenggaraan umrah merupakan salah satu tugas Kementerian Agama sesuai dengan Peraturan Menteri Agama Nomor 18 Tahun 2015 Pasal 20 Ayat (1) dan Ayat (2) disebutkan bahwa  Pengawasan dilakukan oleh Direktur Jenderal atas nama Menteri. Pengawasan meliputi pengawasan terhadap rencana perjalanan, kegiatan operasional pelayanan Jemaah, ketaatan dan/atau penertiban terhadap ketentuan peraturan perundang-undangan. Dalam rangka meningkatkan fungsi pengawasan terhadap pelayanan kepada Jemaah umrah, Kementerian Agama melalui Direktorat Jenderal Penyelenggaraan Haji dan Umrah secara rutin melakukan pemantauan di bandara Soekarno Hatta. Setiap hari menugaskan personil  dari Kementerian Agama bersama Polres Bandara untuk mengawasi langsung aktivitas pelayanan Jemaah di bandara. MoU Kemenag dengan Polri telah berjalan sejak tahun 2013 dan selalu memberikan dukungan penuh. Meningkatkan pengawasan penyelenggaraan umrah. Pengawasan ini dilakukan karena banyaknya biro travel yang menyediakan layanan umrah di indonesia, saat ini pemerintah memang lebih fokus pada penyelenggaraan ibadah haji sehingga menyerahkan penyelenggaraan umrah melalui biro travel. Sementara, kementerian agama hanya berwenang memberikan izin usaha. Adapun yang menjadikan faktor-faktor menyebabkan lemahnya pengawasan oleh kementerian agama terhadap penyelenggaraan ibadah umroh dalam kaitannya dengan kasus PT. Firs anugrah karya wisata ialah Izin Travel Umroh, dan aturan yang belum mampu untuk memenuhui perlindungan konsumen.Adapun upaya-upaya yang dilakukan oleh kementerian agama untuk meningkatkan pengawasan atas usaha biro perjalanan ibadah umroh dalam rangka melindungi jamaah Dengan bentuknya sebagai perseroan terbatas, First Travel merupakan badan usaha yang berbadan hukum, oleh karenanya merupakan subyek hukum yang memiliki hak dan kewajiban. Sebagai subyek hukum, First Travel memiliki tanggung jawab hukum atas dugaan tindak pidana yang telah dilakukannya terhadap para calon jamaah haji dan Umroh, tanggung jawab berhubungan dengan konsep kewajiban hukum. Seseorang bertanggung jawab secara hukum atas sesuatu perbuatan tertentu atau bahwa dia memikul tanggung jawab hukum berarti dia bertanggung jawab atas suatu sanksi dalam hal perbuatan yang bertentangan. Dari aspek hukum, tanggung jawab hukum First Travel dapat dilihat dari aspek perdata, pidana, dan administratif. Kata Kunci: Pengawasan, Penyelenggaraan Perjalanan, Ibadah  Umrah.